Engineered Exosomes for Anti-glioma MicroRNA Delivery in Treatment of GBM. (16th November 2020) - McDonald, Malcolm F; Hossain, Anwar; Momin, Eric N; Hasan, Irtiza; Adachi, Satoshi; Gumin, Joy; Ledbetter, Daniel; Singh, Sanjay K; Daou, Marc; Gopakumar, Sricharan; Kerrigan, Brittany P; Lang, Frederick F
Abstract: INTRODUCTION: We have previously shown that exosomes, naturally occurring nano-size extracellular vesicles, are capable of delivering anti-glioma microRNAs (miRs) to brain tumors. Our studies suggest there is significant opportunity in engineering exosomes to express viral proteins to increase miR packaging efficiency and delivery specificity to glioma cells. METHODS: Engineered exosomes (eExos) were created by transfecting HEK 293 cells with specific viral proteins. Plasmids with either Cre or anti-glioma miRs (miR 124-2, miR 135a-2, and Let7i) were packaged into eExos individually and in combination. For in vitro studies, eExos were incubated with U87 glioma cells harboring a dsRed/eGFP Cre recombinase/LoxP site with change in fluorescent signal used to evaluate packaging and delivery efficacy. Glioma stem cell (GSC) proliferation was assessed with eExos incubated with three GSC lines (GSC 7–11, GSC 8–11, and GSC 231) to evaluate therapeutic efficacy. For in vivo studies, eExos were delivered using a single intratumoral injection into mice harboring GSC 231, and survival analysis was performed. RESULTS: A single dose of eExos with Cre resulted in 82% conversion rate of cells from red to green, demonstrating enhanced packaging, delivery, and expression of Cre compared to control exosomes. eExos with miR plasmids significantly decreased in vitro proliferation in all three glioma cell lines both as individual miRs ( P  < .01) and in miR combination ( P  < .001). Kaplan-Meier survival analysis demonstrated significantly improved survival with eExos packaging miR plasmids both individually and in combination compared to unengineered exosomes packaging miRs ( P  < .01). Specifically, eExos packaged with all three miRs in combination extended median overall survival to 75 days with 20% overall survival compared to 32.5 days in controls ( P  < .001). CONCLUSION: eExos are capable of packaging, delivering, and expressing anti-glioma miR plasmids in various GSCs. eExos packaged with miR plasmids significantly extends median overall survival in a murine glioma model when packaged individually and especially in combination. This treatment strategy may help overcome the current challenge of delivering molecular agents to brain tumors.